Membranous nephropathy successfully treated with a Ponticelli regimen in a patient with HIV: do not assume that a well-known secondary cause is the real cause! - Meng,C (2018)
Idiopathic membranous nephropathy with high-risk criteria for renal disease progression is considered an indication for immunosuppressive treatment. HIV infection has been associated with membranous nephropathy in a minority of patients. A 44-year-old female diagnosed with HIV infection 11 years ago was referred for a nephrology consultation due to nephrotic syndrome. She presented with peripheral edema for 2 months and normal blood pressure. Serum creatinine was 0.74 mg/dL, total cholesterol 490 mg/dL, albumin 2.0 g/dL; urinary examination revealed leukoerythrocyturia and 24h proteinuria was 4.5g. Renal ultrasound showed normal-sized kidneys with preserved corticomedullary differentiation. Kidney biopsy showed thickening of the glomerular basal membrane and staining with Masson trichrome showed sub-epithelial humps. Immunofluorescence was negative except for IgA (+), C3c (+) and IgG (+). A diagnosis of membranous nephropathy was made. Secondary causes, such as neoplasic, infectious and autoimmune, were ruled out. Despite 6 months of conservative measures, proteinuria increased to 11 g/day. Since HIV viral load had been undetectable for several years, along with a CD4+ T cell count persistently above 400/mm3, a modified Ponticelli regimen was started: 3 pulses of methylprednisolone (1g/day), followed by 60 mg of prednisolone/day at months 1, 3 and 5, and cyclophosphamide 200mg/day at months 2, 4 and 6. At the end of the treatment, there was a partial response with proteinuria 3.94 g/day, albumin 3.2 g/dL, and creatinine 0.8 mg/dL. At 48 months of follow-up, the patient is asymptomatic, with creatinine 0.84 mg/dL and proteinuria 0.97 g/day. Conclusion: Membranous nephropathy should be considered in the differential diagnosis in patients with HIV infection complicated by nephrotic syndrome even in the absence of other coinfections and comorbidities typically associated with membranous nephropathy. In patients with sustained negative viral loads and at high risk of progression to end-stage renal disease, in whom secondary causes have been excluded, immunosuppressive therapy might be considered.